La "culinaria" de una investigación (2002)
ABSTRACT: Talking about social research in general or on a particular sector, such as youth, necessarily refers to a range of knowledge and experience almost mysterious in some cases, beyond how many courses on methodology and research techniques have been taken, are purchased primarily for their own practice, but that knowledge and experience are also subject to systematic and transmission of this knowledge - make specific investigator acquires and develops through its practice.